Physical properties of edible coatings and films made with a polysaccharide from Anacardium occidentale L. - Carneiro-da-Cunha, Maria G. (2009)
The effect of the concentrations of the polysaccharide from Anacardium occidentale L. (Policaju) and a surfactant (Tween 80) on relevant properties of edible coatings/films, in view of their application on apples (cv. Golden) was evaluated. The influence of the interactions between those two constituents on apples’ surface properties and on the coating/film’s wettability, water vapor permeability, opacity and mechanical properties was evaluated. The effects of the studied variables (polysaccharide and surfactant concentrations) were analyzed according to a 2² factorial design. Pareto bar charts were used to understand the most significant factors on the studied properties. The addition of surfactant reduced the cohesion forces, therefore reducing the surface tension and increasing the wettability; this resulted in an improved compatibility between the solution and the fruit skin surface. The opacity was also reduced. The results of each of the analyzed properties were adjusted to a polynomial, multifactor model, which provided a good fitting accuracy. This model is important once it will reduce the characterization work needed in subsequent applications of these coatings/films on foods.